Palavras que encantam - Atayde, Joselda de Oliveira; Almeida, Gisele Rodrigues de; Miotto, Jesuína Aparecida Gonçalves; Bordinhão, Andréia Jonceline Chiozini; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf